General practitioners with a special interest in public health; at last a way to deliver public health in primary care - Bradley, S. (BMJ Group, 2005)
Primary care and public health both work to improve the population's health. The potential benefits of improved integration between these disciplines have however not been fully seen because of the lack of a structured way to deliver the integration. This article reviews the benefits, models of working, and challenges to the integration of public health and primary care. General practitioners with special interests (GPwSI) have now been created and formally recognised in clinical roles in the United Kingdom. It is proposed that the creation of GPwSI in public health offers an ideal model of a way of achieving integration and ensuring public health is delivered in primary care.